2021
DOI: 10.1111/jopr.13345
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraoral Scanners for Recording the Denture Bearing Areas: A Systematic Review

Abstract: Purpose To systematically review clinical and laboratory studies that investigated the accuracy of intraoral scanners in recording denture bearing areas. Materials and methods Electronic and manual searches were conducted to identify all the available clinical and laboratory studies reporting the accuracy of digital impressions for recording denture related soft tissues. After the application of predetermined inclusion and exclusion criteria, the final list of articles was reviewed to meet the objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
(138 reference statements)
1
46
0
Order By: Relevance
“…Digital impression data were acquired using an IOS to fabricate the prosthesis. The accuracy of IOSs is reportedly comparable to that of conventional impressions if the unevenness of the residual ridges is sufficient in height and width and is covered with attached mucosa, as in the present case [20]. However, an IOS cannot be used to make pressure impressions of the mucosa on the residual ridge.…”
Section: Discussionsupporting
confidence: 62%
“…Digital impression data were acquired using an IOS to fabricate the prosthesis. The accuracy of IOSs is reportedly comparable to that of conventional impressions if the unevenness of the residual ridges is sufficient in height and width and is covered with attached mucosa, as in the present case [20]. However, an IOS cannot be used to make pressure impressions of the mucosa on the residual ridge.…”
Section: Discussionsupporting
confidence: 62%
“…However, it is difficult to combine digital images because of the lack of clear soft tissue landmarks 45,46 . Recent systematic reviews indicate that the accuracy of IOS for edentulous ridges is comparable to those of conventional methods, even though it is not yet considered an effective alternative to conventional methods unless for preliminary impressions 56 . A clinical study compared the three‐dimensional differences between IOS and conventional impressions of the maxilla and mandible in 10 patients, and reported that superimposition of the scans showed that the differences between the two methods were not statistically significant 57 .…”
Section: Discussionmentioning
confidence: 99%
“…When peripheral borders of conventional impressions were trimmed to the identical extent of the intraoral scan, the resulting accuracy value was improved, and intraoral scans and conventional impressions were reported to be statistically similar. 15,16 Since physical denture retention is obtained by peripheral and inner compression seals, the trimming of the border might compromise the suction of the denture against the tissues. 17 A combination of conventional border molding and an intraoral scan has been described to compensate for the shortcomings of the scan.…”
mentioning
confidence: 99%